ANALYSIS OF THE PERCEPTION OF ROMANIAN CONSUMERS REGARDING THE PRACTICE OF CREATIVE TOURISM AND ITS ROLE IN SUSTAINABLE LOCAL DEVELOPMENT - Liviu MARCUTA; Agatha POPESCU; Cristiana TINDECHE; Cosmina SMEDESCU; Dragos SMEDESCU; Alina MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tourism, as a form of spending free time, has undergone numerous transformations in the last period of time, this is due both to globalization that contributed to the internationalization of tourist experiences, but also to recent events (such as the Covid-19 pandemic, economic crises, etc), but also changing the perception of tourism consumers regarding how they can spend their free time. Traditional or well-known destinations have started to face overcrowding, which is starting to be felt negatively by both residents and visitors who are starting to change their consumption habits regarding the locations they choose as tourist destinations. On the other hand, the challenges of the modern world regarding the effects of global warming, the sharp increase in the population, the depletion of planetary resources, but also the much greater concerns of the current generations regarding these aspects, make the choices we make regarding the choice leisure destinations to change and become more responsible. In this context, creative tourism as an increasingly sought-after option, among a growing category of consumers. In this paper, we set out to analyze the perception that tourism consumers in Romania have regarding this form of tourism. The research assumed, on the one hand, a bibliographic analysis regarding the term creative tourism and how this notion has evolved from the moment of its definition as a form of tourism in the 2000s until now, as well as from a study of case based on the application of a questionnaire to measure the perception of consumers regarding this form of tourism, but especially on the awareness of its existence. The questionnaire had 16 questions answered by 124 respondents. The data were centralized and interpreted with the help of the Excel program, the results highlighting the fact that although some of the respondents practice creative tourism, it is quite little known as a concept. The answers given by the study participants highlighted the fact that they are interested in practicing activities integrated into creative tourism, considering that there are many advantages both regarding the experiences they create, with the interactions they establish with the locals or with the other participants. At the same time, the impact that creative tourism practices have at the local level (both economic and social) is recognized. We consider that these results are useful not only at the micro level, but also at the macro level, under the conditions that the development strategies of the field of hospitality will be thought in such a way as to promote, integrate and develop this form of contemporary tourism.